ChemInform Abstract: Multifunctionalization of Alkenes via Aerobic Oxynitration and sp3 C—H Oxidation. Issue 25 (3rd June 2013) - Taniguchi, Tsuyoshi; Sugiura, Yuki; Hatta, Takashi; Yajima, Atsushi; Ishibashi, Hiroyuki
Abstract The catalyst‐free aerobic oxynitration of different substrates is reported [13 examples].